The Sophistic Esprit Français: Sophistry and Elite French Humanistic Education - Jonathan Doering (Humanities)
This essay examines the role of sophistic practices in elite French humanistic education, specifically “omniloquacity”, the ability to speak about any given subject. Drawing together intellectual history, cross-cultural comparisons, and educational testimonies, the essay elaborates a “pedagogical” version of sophistry in this French context that differs from more traditional “vocational” sophistries. Although I focus on the mid-twentieth century, I also consider earlier upheavals and Jesuit influences that shaped an agonistic culture of sophistic performances, challenging competitions, and ultimately, a certain esprit français associated with elite humanistic education. The history of rhetoric in France does not end with the demise of the rhetoric class in 1902, and takes on new meanings when considering the sophistic practices that outlived its nominal death.